Nurse infected with Covid-19 from a provisional dengue patient - Wisit Prasitsirikul; Krit Pongpirul; Wannarat A. Pongpirul; Nayot Panitantum; Anuttra C. Ratnarathon; Thiravat Hemachudha (Emerging Microbes and Infections)
We report a 35-year-old female nurse who possibly received the SARS-CoV-2 virus during the blood sampling of a 35-year-old male patient initially suspected as a dengue infection. The patient had mild thrombocytopenia and positive dengue IgG and IgM whereas the clinicians were not aware of the possibility of false-positive dengue serology revealed in the published case report from Singapore. The nurse put on a pair of gloves but did not wear a mask during the only encounter with this patient. This nosocomial transmission raised a safety concern among healthcare professionals in an area with a relatively low Covid-19 prevalence, especially when the clinical and laboratory characteristics could be confused with other viral infections.